2023
DOI: 10.3390/nu15071741
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Association of the Adequacy and Balance Scores in the Modified Healthy Eating Index with Type 2 Diabetes in Women

Abstract: Type 2 diabetes (T2DM) has markedly increased among Asians as their diets and lifestyles become more westernized. We, therefore, investigated the hypothesis that the Korean healthy eating index (KHEI) scores are associated with gender-specific T2DM risk in adults. The hypothesis was tested using the data from the Korea National Health and Nutrition Examination Survey-VI (2013–2017) with a complex sample survey design. Along with the KHEI scores, the modified KHEI (MKHEI) scores for the Korean- (KSD) and Wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The Korean Healthy Eating Index (KHEI), based on Korean dietary guidelines, was developed to assess the overall dietary quality, reflecting regional dietary practices and culture. Previous studies have shown that low KHEI scores are associated with metabolic diseases [19] and type 2 diabetes [20]. However, to the best of our knowledge, the association between temporary employment and the KHEI has not yet been explored.…”
Section: Introductionmentioning
confidence: 93%
“…The Korean Healthy Eating Index (KHEI), based on Korean dietary guidelines, was developed to assess the overall dietary quality, reflecting regional dietary practices and culture. Previous studies have shown that low KHEI scores are associated with metabolic diseases [19] and type 2 diabetes [20]. However, to the best of our knowledge, the association between temporary employment and the KHEI has not yet been explored.…”
Section: Introductionmentioning
confidence: 93%